Aggregation behaviour of hydrophobically modified polyacrylate – Variation of alkyl chain length. (23rd July 2015) - Riemer, Sven; Prévost, Sylvain; Dzionara, Michaela; Appavou, Marie-Sousai; Schweins, Ralf; Gradzielski, Michael
Abstract: The aggregation behaviour in aqueous solution of hydrophobically modified polyacrylates, synthesized by Atomic Transfer Radical Copolymerisation (ATRP) of mixtures of alkyl acrylate and t-butyl acrylate and subsequent hydrolysis of the t-butyl acrylate, was investigated by a combination of static and dynamic light scattering with small-angle neutron scattering (SANS). The degree of amphiphilicity was varied by the percentage of alkyl chains and the length of the alkyl chain (butyl to dodecyl), and, in addition, depends strongly on pH via the ionization of the polyacrylate backbone. SANS shows the formation of hydrophobic domains whose size scales with the length of the alkyl chain. The tendency for domain formation increases with the length of the alkyl chains and is much more pronounced for lower pH, while at high pH the electrostatic charging suppresses the formation of hydrophobic domains for chains shorter than octyl. Then only relatively large and loosely connected aggregates are formed. These hydrophobically modified copolymers show a pronouncedly pH dependent aggregation behaviour that is controlled by the length and percentage of hydrophobic modification and this widely tuneable aggregation behaviour could be interesting for the transport and controlled release of hydrophobic cargo molecules. Graphical abstract: Highlights: Amphiphilic copolymers with different hydrophobic side chains were synthesised. Self-assembly can be tuned by molecular architecture. Aggregation behaviour can be controlled by pH. Structure controlled by a delicate balance of electrostatic and hydrophobic forces. Size of hydrophobic domains is given by the hydrophobic alkyl chain.